An Overview of Video Lecturer on Practical Subjects During the COVID-19 Pandemic - Umi Budi Rahayu (Universitas Muhammadiyah Surabaya, 2020)
The COVID-19 pandemic also had an impact on educational aspects, especially the teaching system in lectures. The purpose of this paper was to find an overview of lectures in online using video media at the Practice of Manipulation Therapy Subject during the COVID-19 pandemic. Observational study with a structured questionnaire related a description of practical lectures for 73 students of Physiotherapy Department that distributed via Google Form. Online teach techniques using google.meet displayed lecturer’s explanations related to teaching materials in accordance with the teaching plan on the video media about an application of manipulation therapy that have been made by previous lecturers. An overview of the results was displayed as a percentage and described descriptively. The results showed 84.9% of students agreed that online practice lectures using video media. Specifically for the practice manipulation therapy subject was 97.3% of students agreed to use video media. Regarding the understanding of material that enough and can understand were 60.3% and 23.3% respectively. There were obstacles so that the percentage of students who state not easy and easy to practice at home were 68.5% and 24.7%, respectively. There were 95.9% of students stated that video media made it easier to understand because it could be played back, even though some students revealed signal difficulties. Even so, 100% of students still want practice lectures to be done offline. The conclusion showed an overview of online lectures with video media for practical subjects during the COVID-19 pandemic as an option under the choice of offline practice learning.